Current account: mean-reverting or random walk behavior? - Lau, Evan; Ahmad Zubaidi, Baharumshah; Chan, Tze Haw (North-Holland, 2006)
This paper sets out to investigate the statistical properties of current account in the crisis-affected countries of East Asian (Asian-5: Indonesia, Korea, Malaysia, the Philippines and Thailand) utilizing data from 1976Q1 to 2001Q4. We split the full sample period into two sub-periods of the pre-crisis (1976Q1–1996Q4) and post-crisis (1997Q1–2001Q4) eras. Univariate unit root tests indicate that current account follows a non-stationary process under both eras. However, using more sophisticated panel techniques revealed that the current account displays mean-reverting property in all three sampling periods. Meanwhile, deviations of half-life estimates in the full sample period (post-crisis) were found to be much more rapid compared to the pre-crisis period. Our major conclusions are first, the empirical evidence supports the modern intertemporal approach to current account. Second, the results reveal that the Asian-5 current accounts were on a sustainable path, even during the pre-crisis period, hence, questioning the notion that the East Asian financial crisis was due to the mismanagement of external imbalances.